Efikasi ekstrak tanaman obat Binahong Anredera cordifolia (Ten) Steenis untuk meningkatkan pertumbuhan ikan Nila Oreochromis niloticus - Wantah, Monika M.; Longdong, Sammy N.J.; Kreckhoff, Reni L.; Mantiri, Desy M.H.; Tumbol, Reiny A.; Manoppo, Henky (e-Journal BUDIDAYA PERAIRAN, 2018)
The aim of this research was to study the effect of Binahong extract on the growth of Nile tilapia. A number of 225 fish measuring 10-12 cm in length with an average weight of 15 g was obtained from Fishery Development Center and Training, Tateli. The fish were put  in oxygenated plastic bags and transported to Laboratory of Aquaculture Technology. The fish was kept in aquarium equipped with an aerator with a density of 15 fish per aquaria. The test material used was the stem of Binahong plant stem, macerated with alcohol 70% for 3 days. The extract was then filtered with whatman filter paper and extract was concentrated using a Rotary Evaporator. The extract was further diluted to obtain  concentrations of 12.5, 25, 50, and 100 mg / mL Binahong  extract as treatment was given to the fish after mixed first into the pellet. The fish was fed with treatment feed for 30 days. Control feed was not supplemented with binahong extract. Growth data was measured at day 30 after treatment. The results showed that the extract of binahong had significant effect on fish growth (p <0.01) with the best result achieved at concentration of 100 mg/mL. In conclusion, supplementation of  binahong extract into fish feed could improve growth of  fish in which the best growth was obtained in fish fed diet containing 100 mg/mL of binahong extract.Keywords: Medicinal plants, tilapia, Anredera cordifolia, growth, maceration